Controlled preparation of NiCo-LDH@CuCo2O4/Ti3C2 core−shell structure for high performance asymmetric supercapacitor. (10th November 2022) - Zhao, Yanan; Zhang, Yao; Wang, Qinqin; Song, Yuli; Zhang, Yaqian; Liu, Lizhi; Li, Wenze
ABSTRACT: In this work, NiCo-LDH@CuCo2 O4 /Ti3 C2 core–shell structured electrode materials are grown on Ni foam by hydrothermal routes. The as-prepared electrode exhibited an ultra-high gravimetric capacitance of 3480 mF cm −2 with good reversibility. The excellent performances can be attributed to the unique heterogenous structure. An asymmetric hybrid supercapacitor is assembled by using NiCo-LDH@CuCo2 O4 /Ti3 C2 as the positive electrode and activated carbon as the negative electrode. The ASC presents high energy density (0.72 mW h cm −3 at a power density of 57.6 mW cm −3 ) and a capacity retention of 99.5% after 6000 cycles.